The effect of Nordic hamstring exercise intervention volume on eccentric strength and muscle architecture adaptations: A systematic review and meta-analyses - Cuthbert, M.; Ripley, N.; McMahon, J. J.; Evans, M.; Haff, G. G.; Comfort, P. (Sports Medicine, 2020)
Although performance of the Nordic hamstring exercise (NHE) has been shown to elicit adaptations that may reduce hamstring strain injury (HSI) risk and occurrence, compliance in NHE interventions in professional soccer teams is low despite a high occurrence of HSI in soccer. A possible reason for low compliance is the high dosages prescribed within the recommended interventions. The aim of this review was to investigate the effect of NHE-training volume on eccentric hamstring strength and biceps femoris fascicle length adaptations. Methods: A literature search was conducted using the SPORTDiscus, Ovid, and PubMed databases. A total of 293 studies were identified prior to application of the following inclusion criteria: (1) a minimum of 4 weeks of NHE training was completed; (2) mean ± standard deviation (SD) pre- and post-intervention were provided for the measured variables to allow for secondary analysis; and (3) biceps femoris muscle architecture was measured, which resulted in 13 studies identified for further analysis. The TESTEX criteria were used to assess the quality of studies with risk of bias assessment assessed using a fail-safe N (Rosenthal method). Consistency of studies was analysed using I2 as a test of heterogeneity and secondary analysis of studies included Hedges` g effect sizes for strength and muscle architecture variables to provide comparison within studies, between-study differences were estimated using a random-effects model. Results: A range of scores (3-11 out of 15) from the TESTEX criteria were reported, showing variation in study quality. A `low risk of bias` was observed in the randomized controlled trials included, with no study bias shown for both strength or architecture (N = 250 and 663, respectively; p < 0.001). Study consistency was moderate to high for strength (I2 = 62.49%) and muscle architecture (I2 = 88.03%). Within-study differences showed that following interventions of = 6 weeks, very large positive effect sizes were seen in eccentric strength following both high volume (g = 2.12) and low volume (g = 2.28) NHE interventions. Similar results were reported for changes in fascicle length (g = 2.58) and a large-to-very large positive reduction in pennation angle (g = 1.31). Between-study differences were estimated to be at a magnitude of 0.374 (p = 0.009) for strength and 0.793 (p < 0.001) for architecture. Conclusions: Reducing NHE volume prescription does not negatively affect adaptations in eccentric strength and muscle architecture when compared with high dose interventions. These findings suggest that lower volumes of NHE may be more appropriate for athletes, with an aim to increase intervention compliance, potentially reducing the risk of HSI.